2016
DOI: 10.1525/mp.2016.33.3.319
|View full text |Cite
|
Sign up to set email alerts
|

A Neurodynamic Account of Musical Tonality

Abstract: Science since antiquity has asked whether mathematical relationships among acoustic frequencies govern musical relationships. Psychophysics rejected frequency ratio theories, focusing on sensory phenomena predicted by linear analysis of sound. Cognitive psychologists have since focused on long-term exposure to the music of one’s culture and short-term sensitivity to statistical regularities. Today evidence is rapidly mounting that oscillatory neurodynamics is an important source of nonlinear auditory responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 5 publications
1
37
0
3
Order By: Relevance
“…In this approach, metrical expectations emerge from the resonance of coupled oscillators that entrain to temporal periodicities in the stimulus. A related oscillatory approach has been used to predict cross‐cultural invariances in perceived tonal stability . Since these models naturally imply an explanation of pitch and temporal processing in terms of stimulus structure, they do not provide a compelling account of enculturation (though it has been claimed that it is potentially compatible with Hebbian learning) .…”
Section: Idyommentioning
confidence: 99%
See 1 more Smart Citation
“…In this approach, metrical expectations emerge from the resonance of coupled oscillators that entrain to temporal periodicities in the stimulus. A related oscillatory approach has been used to predict cross‐cultural invariances in perceived tonal stability . Since these models naturally imply an explanation of pitch and temporal processing in terms of stimulus structure, they do not provide a compelling account of enculturation (though it has been claimed that it is potentially compatible with Hebbian learning) .…”
Section: Idyommentioning
confidence: 99%
“…A related oscillatory approach has been used to predict cross-cultural invariances in perceived tonal stability. 75 Since these models naturally imply an explanation of pitch and temporal processing in terms of stimulus structure, they do not provide a compelling account of enculturation (though it has been claimed that it is potentially compatible with Hebbian learning). 71 It is possible that oscillatorbased models and the mechanisms of statistical learning and probabilistic processing implemented in IDyOM are complementary in simulating different aspects of expectation (e.g., enculturated versus nonenculturated processing) or by operating at different Marrian levels of description.…”
Section: Idyommentioning
confidence: 99%
“…In general, low-order mode locking at a simple frequency ratio (i.e., with k and m being small integers) is stronger and more stable with a wider locking region than high-order mode locking at a more complex ratio (large k and m) [34]. This property of nonlinear resonance has been suggested to underlie the relative consonance and dissonance of musical intervals [21] and the tonal stability of pitches in musical keys [23,24]. In the latter studies, the coefficient to the input term in Eq.…”
Section: B Comparison Of Mode Locking Rangesmentioning
confidence: 99%
“…It has been shown that auditory neurons modelock to acoustic stimulation [17,18], and human auditory brainstem responses include various mode-locking ratios to stimulus frequenices [19]. Mode locking in the auditory system was recently proposed as a basis for the perception of pitch [20], harmony [21,22], tonality [23,24], and rhythm and meter [25][26][27], which have been traditionally related to frequency ratios (see Section IV B for more discussion).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation